Analisis Kemampuan Literasi Numerasi Ditinjau Dari Gaya Belajar Pada Siswa VI SDN 55/1 Sridadi - Nurhalisa, Intan; Eka Sasrawati; Violita Zahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze students’ numeracy literacy abilities in terms of learning styles among sixth-grade students at SDN 55/1 Sridadi. Numeracy literacy is a fundamental skill required in the twenty-first century and is emphasized in the Kurikulum Merdeka as part of the national education goals. The study employed a qualitative descriptive approach to explore how differences in learning styles visual, auditory, and kinesthetic affect students’ ability to understand and solve numeracy-based contextual problems. Data were collected through observation, interviews, and documentation involving selected students representing each learning style. The collected data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings show that students with visual learning styles demonstrate better ability in reading and interpreting graphs or numerical data, auditory learners excel in solving problems through listening and verbal explanation, while kinesthetic learners show strength in tasks involving hands-on activities and direct experience. The study also found that students’ strategies in solving numeracy literacy problems varied according to their learning styles, particularly in answering Asesmen Kompetensi Minimum (AKM)-based tasks. These results indicate that teachers should recognize the diversity of students’ learning styles and integrate differentiated instruction in classroom activities. By implementing learning strategies aligned with students’ learning styles, teachers can enhance students’ understanding, engagement, and achievement in numeracy literacy effectively and inclusively.